REVITALISASI PERAN ICMI PADA ERA REFORMASI - Juju Saepudin (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2016)
The birth and the existence of the Association of Indonesian Muslim Intellectuals (ICMI) has become a phenomenon in the politics of Islam in Indonesia, especially about its existence and its influence after the collapse of the New Order era. This paper presents the results of research related to the dynamics of ICMI in the Reformation Era. With qualitative approach and descriptive analysis, it can be concluded that in the Reformation Era, ICMI has decreased its influence and its appeal because their failure in making one of the power house in the national politics prior to the fall of the New Order Era and to have the clash of political functions and religious functions resulting in the identity loss of ICMI. Therefore, it is important to revitalize ICMI role as an agent of social change, in order that ICMI can play a major role in the dynamics of political Islam and nation-building in the field of religion, social, politic, education and empowerment of civil society in Indonesia towards civil society.